2022
DOI: 10.3390/ijms231810430
|View full text |Cite
|
Sign up to set email alerts
|

Natural Xylooligosaccharides Exert Antitumor Activity via Modulation of Cellular Antioxidant State and TLR4

Abstract: It has been recently proven that xylooligosaccharides (XOS) with prebiotic properties have diverse beneficial biological effects including immunomodulatory and antitumor activities. The present article focused on the chemical and biological evaluation of corn-derived commercially available XOS and aimed to elucidate their cytotoxicity and inhibitory potential against tumor cells. Spectrophotometric chemical analyses, Fourier transform infrared spectroscopy, and high-performance liquid chromatography analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Furthermore, the E1, which contains enzymatically degraded xylose products, only suppressed the secretion of IL-6. Indeed, several studies [ 38 , 39 , 40 ] reported that xylose and xylo-oligosaccharides extracted from algae strongly suppressed IL-6 secretion among the cytokines produced in LPS-stimulated macrophages, compared to TNF-alpha and IL-1B.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the E1, which contains enzymatically degraded xylose products, only suppressed the secretion of IL-6. Indeed, several studies [ 38 , 39 , 40 ] reported that xylose and xylo-oligosaccharides extracted from algae strongly suppressed IL-6 secretion among the cytokines produced in LPS-stimulated macrophages, compared to TNF-alpha and IL-1B.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the degree of polymerization (DP) or the number of sugar units in a prebiotic molecule also affects its fermentability and prebiotic index score. Prebiotics with a low DP, such as FOS (DP of 2 to 8), GOS (DP of 2 to 8), and XOS (DP of 2 to 10), tend to be more fermentable and have a higher prebiotic index score than prebiotics with a high DP, such as INU (DP of 2 to 60) [ 44 , 45 , 46 ]. This is because the longer one contains fewer non-reducing ends per unit mass than the shorter one, resulting in less substrate for hydrolysis by bacterial enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 1,4-D-Xylobiose’s anticancer effects are mediated via the modulation of glutathione homeostasis and TLR4 signaling, which impact cellular redox status. Therefore, it might be assumed that this chemical compound is also responsible for our plant’s carcinogenic properties [ 19 ]. The LC-MS analysis of the methanolic extract from O. baccatus branches identified 13 major compounds, and some of them are thought to be responsible for the extract’s antibacterial and anticancer activities ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%